2021
DOI: 10.20944/preprints202108.0328.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Prevention and Treatment of Methotrexate-induced Hepatotoxicity: Potential of Natural Phytobioactive Compounds<strong> </strong>

Abstract: Methotrexate (MTX) is a potent drug for the treatment of various diseases globally amidst being a chemotherapeutic and immunosuppressant agent. However, hepatotoxicity induced by MTX could be life-threatening if left untreated. Folate supplementation is concurrently applied to reduce the adverse effects of MTX, albeit efficacy compromise. Therefore, there is the need to understand the process for the prevention and treatment strategies for MTX induced hepatotoxicity (MIH). In recent times, preliminary preclini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 67 publications
(80 reference statements)
0
1
0
Order By: Relevance
“…Furthermore, it has been demonstrated that TNF-α is Life 2023, 13, 1173 2 of 15 crucial for maintaining liver equilibrium and links inflammation to apoptosis. According to previous studies, elevated levels of TNF-α, IL-6, and other cytokines trigger apoptotic pathways resulting in methotrexate-induced hepatotoxicity [13,14]. MTX is reported to cause hepatotoxicity when used for a prolonged period, even at a minimal dosage [15].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it has been demonstrated that TNF-α is Life 2023, 13, 1173 2 of 15 crucial for maintaining liver equilibrium and links inflammation to apoptosis. According to previous studies, elevated levels of TNF-α, IL-6, and other cytokines trigger apoptotic pathways resulting in methotrexate-induced hepatotoxicity [13,14]. MTX is reported to cause hepatotoxicity when used for a prolonged period, even at a minimal dosage [15].…”
Section: Introductionmentioning
confidence: 99%